Pregnancy in multiple endocrine neoplasia type 1 equals multiple complications. (September 2014) - Mistry, Megha; Gupta, Manish; Kaler, Mandeep
Multiple endocrine neoplasia type 1 (MEN 1) is a rare inherited disorder caused by mutations in the tumour suppressor gene MEN 1. It is characterised by a predisposition towards the development of parathyroid, anterior pituitary and entero-pancreatic tumours. Clinically, MEN 1 is defined following development of two out of these three tumours. There have been no published cases of the management of MEN 1 in pregnancy. We report the first case of a 31-year-old primigravida with a confirmed diagnosis of MEN 1 prior to conception. Due to the rare nature of MEN 1, there are no guidelines on how such women should be managed. The main issues were to assess and manage potential complications, such as hypercalcaemia, diabetes mellitus and the symptoms from a pituitary tumour as well the issues around a gastrinoma and monitor fetal well-being. A Caesarean section was performed at 35 weeks gestation for a growth-restricted fetus with raised umbilical artery Dopplers. The neonate was treated with intravenous calcium secondary to hypocalcaemia. The patient and neonate recovered well. We have demonstrated successful management of a woman with MEN 1 who completed her pregnancy with few complications and a healthy neonate. It is vital for such women to be managed in the context of a multidisciplinary team setting to optimise maternal and fetal outcomes.